A Comprehensive Study of Neutralizing Antigenic Sites on the Hepatitis E Virus (HEV) Capsid by Constructing, Clustering, and Characterizing a Tool Box - Zhao, Min (J Biol Chem, 2015)
The hepatitis E virus (HEV) ORF2 encodes a single structural capsid protein. The E2s domain (amino acids 459–606) of the capsid protein has been identified as the major immune target. All identified neutralizing epitopes are located on this domain; however, a comprehensive characterization of antigenic sites on the domain is lacking due to its high degree of conformation dependence. Here, we used the statistical software SPSS to analyze cELISA (competitive ELISA) data to classify monoclonal antibodies (mAbs), which recognized conformational epitopes on E2s domain. Using this novel analysis method, we identified various conformational mAbs that recognized the E2s domain. These mAbs were distributed into 6 independent groups, suggesting the presence of at least 6 epitopes. Twelve representative mAbs covering the six groups were selected as a tool box to further map functional antigenic sites on the E2s domain. By combining functional and location information of the 12 representative mAbs, this study provided a complete picture of potential neutralizing epitope regions and immune-dominant determinants on E2s domain. One epitope region is located on top of the E2s domain close to the monomer interface; the other is located on the monomer side of the E2s dimer around the groove zone. Besides, two non-neutralizing epitopes were also identified on E2s domain that did not stimulate neutralizing antibodies. Our results help further the understanding of protective mechanisms induced by the HEV vaccine. Furthermore, the tool box with 12 representative mAbs will be useful for studying the HEV infection process.